2013
DOI: 10.1038/nn.3429
|View full text |Cite
|
Sign up to set email alerts
|

Arc in the nucleus regulates PML-dependent GluA1 transcription and homeostatic plasticity

Abstract: The activity-regulated cytoskeletal protein Arc/Arg3.1 is required for long-term memory formation and synaptic plasticity. Arc expression is robustly induced by activity, and Arc protein localizes both to active synapses and the nucleus. While its synaptic function has been examined, it is not clear why or how Arc is localized to the nucleus. We found that murine Arc nuclear expression is regulated by synaptic activity in vivo and in vitro. We identified distinct regions of Arc that control its localization, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
197
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(206 citation statements)
references
References 53 publications
(92 reference statements)
9
197
0
Order By: Relevance
“…This protein is upregulated by synaptic activity thereby controlling the degradation of Arc, a protein involved in AMPAR endocytosis (Greer et al, 2010). Arc protein is also involved in the mGluRdependent long-term depression through AMPAR endocytosis (Waung et al, 2008), and its nuclear localization regulates homeostatic plasticity by decreasing GluA1 transcription (Korb et al, 2013). Knockout mouse models for Ube3A have reduced hippocampal synaptic GluA1 receptors with a concomitant decrease in AMPAR mediated current, and reduced levels of mESPC (Greer et al, 2010).…”
Section: Role Of Ups In Nervous Systemmentioning
confidence: 99%
“…This protein is upregulated by synaptic activity thereby controlling the degradation of Arc, a protein involved in AMPAR endocytosis (Greer et al, 2010). Arc protein is also involved in the mGluRdependent long-term depression through AMPAR endocytosis (Waung et al, 2008), and its nuclear localization regulates homeostatic plasticity by decreasing GluA1 transcription (Korb et al, 2013). Knockout mouse models for Ube3A have reduced hippocampal synaptic GluA1 receptors with a concomitant decrease in AMPAR mediated current, and reduced levels of mESPC (Greer et al, 2010).…”
Section: Role Of Ups In Nervous Systemmentioning
confidence: 99%
“…Thus, we hypothesize that the increased expression of Arc/Arg3.1 in the whole homogenate may depend not only on its enhancement in the crude synaptosomal fraction (Giannotti et al, 2013b) but also on the up-regulation herein observed in the nuclear fraction. Also, the increase of nuclear Arc/Arg3.1 might participate to the regulation of glutamate AMPA receptors since we observed reduced Gria1 transcription, which in turn may lead to reduced GluA1 synthesis, adding novel evidence to the inverse relationships existing between Arc/Arg3.1 and AMPA receptors following long-term cocaine withdrawal (Giannotti et al, 2013b;Korb et al, 2013).…”
Section: Resultsmentioning
confidence: 57%
“…4C). While these changes may contribute to explain Arc/Arg3.1 up-regulation, we next measured the transcription of Gria1, the main glutamate AMPA receptor subunit, a target of increased nuclear Arc/Arg3.1 expression (Korb et al, 2013). Indeed, we found reduced Gria1 mRNA levels (-21%, p<0.05) (Fig.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations